Iowa Birdline update, November 6, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for November 6, 1989. Highlights include the sighting of a Black-headed Gull as waterfowl migration reaches full swing. Epson - sheet feed/flatbed